2003
DOI: 10.1046/j.1365-2648.2003.02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a self‐management course for patients with systemic lupus erythematosus

Abstract: The systemic lupus erythematosus self-management course had effects in reducing fatigue and depression and improving coping skills and self-efficacy. This course is potentially a good nursing intervention that can be offered in community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 17 publications
1
57
1
3
Order By: Relevance
“…So far, relatively few studies have been carried on compared to what has been done with other chronic diseases (Sohng, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, relatively few studies have been carried on compared to what has been done with other chronic diseases (Sohng, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a subset of patients (approximately 40%) that remain in discomfort and they can benefit from psychosocial interventions (Dobkin et al, 2001). None of the studies found significant immunological changes in the index of disease activity (Navarrete-Navarrete et al, 2010;Sohng, 2003).…”
Section: Pre-and Post-test (N=10)mentioning
confidence: 93%
See 2 more Smart Citations
“…Fatigue usually occurs before the other findings develop and it is the most important problem in one-third of patients. [8,9] Fatigue is a constant problem and causes a decrease in functions. [10,11] Fatigue affects activities, physical functions and working life and thus causes a decrease in the quality of life.…”
Section: Introductionmentioning
confidence: 99%